Inverse association between obesity and suicidal death risk - Joonyub Lee; Seung-Hwan Lee; Mee-Kyoung Kim; Hyuk-Sang Kwon; Jae-Seung Yun; Yeoree Yang; Kun-Ho Yoon; Jae-Hyoung Cho; Chi-Un Pae; Kyungdo Han; Jang Won Son (BMC Psychiatry)
Abstract Background Suicide is a significant yet preventable public health issue. Body mass index (BMI) is a readily measurable indicator associated with various health outcomes. However, the relationship between BMI and suicidal death risk is complex and warrants further investigation, particularly within contemporary, non-Western contexts with consideration of potential confounders. The purpose of this study was to investigate the relationship between BMI and the risk of suicidal death. Methods This study was nationwide, retrospective, observational study based on Korean National Health Insurance Service database. We analyzed 4,045,081 participants who were aged > 19 years and underwent national health surveillance in 2009. The participants were categorized according to their BMI (underweight: < 18.5 kg/m², normal weight: 18.5–23 kg/m², overweight: 23–25 kg/m², class I obesity: 25–30 kg/m², and class II obesity: > 30 kg/m²). The primary outcome was the death events caused by suicide which was defined by International Classification of Disorders (ICD-10) codes (X60–X84) and death records documented by the Korea National Statistical Office. Multivariate Cox proportional hazard regression analysis was performed to estimate the risk of suicidal death with respect to BMI categories after adjusting for potential confounders (age, sex, income, diabetes, hypertension, dyslipidemia, smoking, drinking, exercise, self-abuse, waist circumference, schizophrenia, bipolar disorder, eating disorder, cancer, anxiety, and substance use disorder). Results Underweight individuals had an increased risk (hazard ratio [HR] 1.44, 95% confidence interval [CI] 1.31–1.57) while overweight (HR 0.79, 95% CI 0.76–0.83), class I (HR 0.76, 95% CI 0.71–0.80) and class II obesity (HR 0.71, 95% CI 0.63–0.81) were associated with decreased risks of suicidal deaths compared to those of the normal weight individuals (BMI 18.5–23). This trend was consistent regardless of the presence of major depressive disorder (MDD) or the type of living arrangements of the participants. Conclusions Suicidal death risk was inversely correlated with BMI categories, independent of MDD or living arrangements. Our data suggests the importance of physiological factors associated with body mass in understanding suicidal death risk. Furthermore, these data provide valuable insights to where the public health resources should be invested to reduce suicidal death rates.